Catena-Poly {N,N-dimethyl-N '- 1-(pyridin-2-yl)ethylidene ethane-1,2-diamine-kappa(3) N,N ',N ''}(thiocyanato-kappa N)cadmium -mu-thiocyanato-kappa(2) S:N - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
In the title compound, [Cd(NCS)(2)(C11H17N3)] (n) , the CdII atom is octahedrally coordinated by the N,N',N''-tridentate Schiff base ligand and one terminal thiocyanate N atom. Two trans-N:S-bridging thiocyanates complete the N5S donor set around the Cd atom. In the crystal, adjacent CdII ions are linked by the thiocyanate N:S-bridges into polymeric chains along the c axis.